Mangrove forest composition, diversity, and disturbances in Carcar City and Sibonga Municipality, Southern Cebu Island, Philippines - EDGARDO P. LILLO; ARCHIEBALD B. MALAKI; STEVE MICHAEL T. ALCAZAR; MARIA LEVY M. CHAVEZ; RAAMAH ROSALES; CHRISTINE JOY TOMOL; ERWIN M. PANTINOPLE; BERNARDO R. REDOBLADO; MARVIN A. MARGATE; JOHN LOU DIAZ; JETHER L. ISABELO; BEATRICE NICOLE R. CAGARA; MICHELLE ABRIGANA; JIMMY E. MAGO; DEMETRIO M. CAÑARIJO III; IAN REY G. SANCHEZ; MARIA ERICKA OBANDO; JACINTO BELAÑIZO; ROLAND BECERIL; JENELYN CARREON; GLORY GRACE G. DIAZ; CHRISTINE FAYE O. GONZAGA; CHERYLEN R. DAVIRAO; MARY JANE S. REVILLAS; JOHN MARK LIM; EDUARD P. LILLO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Lillo EP, Malaki AB, Alcazar SMT, Chavez MLM, Rosales R, Tomol CJ, Pantinople EM, Redoblado BR, Margate MA, Diaz JL, Isabelo JL, Cagara BNR, Abrigana M, Mago JE, Cañarijo III DM, Sanchez IRG, Obando ME, Belañizo J, Beceril R, Carreon J, Diaz GGG, Gonzaga CFO, Davirao CR, Revillas MJS, Lim JM, Lillo EP. 2024. Mangrove forest composition, diversity, and disturbances in Carcar City and Sibonga Municipality, Southern Cebu Island, Philippines. Biodiversitas 25: 2035-2043. Mangrove forests are one of the world’s most vulnerable tropical ecosystems. The study assessed the mangrove forest composition, diversity, and disturbances in Sibonga Municipality and Carcar City, Cebu Island, Philippines, as a basis for its conservation planning. A transect line was established for a minimum length of 1000 m and a maximum of 2000 m (seaward, middleward, and landward), at an interval of 100 meters. A 10 × 10 m quadrant was established within the transect line at 250 m intervals resulted in a total of 108 plots. Disturbances and threats in two sampling sites were evaluated through direct field observations and interview, and analyzed using the Beynen and Townsend disturbance index. The study identified 22 true mangrove species categorized into 11 families and 14 genera with Excoecaria agallocha L., Sonneratia alba Sm., Rhizophora apiculata Blume, and Avicennia marina (Forssk.) Vierh dominating both sites. The endangered Pemphis acidula J.R.Forst. & G.Forst. was recorded in Sibonga. Aside from low diversity, both sites exhibited a high disturbance index due to illegal activities such as cutting, charcoal production, and land conversion. Such disturbances affects biodiversity and threatens coastal community. Urgent local government action is needed to preserve these ecosystems, emphasizing awareness and community involvement for long-term survival.